1989
DOI: 10.1136/jech.43.4.352
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of non-T cell acute lymphoblastic leukaemia of children in Hokkaido, Japan.

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 9 publications
3
54
2
Order By: Relevance
“…In contrast with four previous studies (Kneale et al, 1986;McKinney et al, 1987;Nishi and Miyake, 1989;Kaatsch et al, 1996), our data provide no evidence of a reduced ALL risk following vaccination with DTP, MMR, or OPV. Our failure to detect such inverse associations may be due to a lack of statistical power, because DTP, MMR and OPV were nearly universal among both cases and controls.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In contrast with four previous studies (Kneale et al, 1986;McKinney et al, 1987;Nishi and Miyake, 1989;Kaatsch et al, 1996), our data provide no evidence of a reduced ALL risk following vaccination with DTP, MMR, or OPV. Our failure to detect such inverse associations may be due to a lack of statistical power, because DTP, MMR and OPV were nearly universal among both cases and controls.…”
Section: Discussioncontrasting
confidence: 56%
“…Our study differed in several methodologic aspects from previous investigations. Only one previous study (Innis, 1965) obtained vaccine data from written records, only one (Kneale et al, 1986) included more cases, and only two (Nishi and Miyake, 1989;Kaatsch et al, 1996) focused specifically on ALL. While four of the previous studies (Kneale et al, 1986;McKinney et al, 1987;Nishi and Miyake, 1989;Kaatsch et al, 1996) utilized age-matched controls, only one (Kaatsch et al, 1996) adjusted for socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of the association between fewer routine immunizations and leukaemia can be explained by reporting bias as mentioned above and by prodromal manifestations of the malignancy preventing the conduct of regular immunization schemes. Previous studies have been inconsistent on this topic, while some found evidence that immunizations convey protection (Kneale et al, 1986;Hartley et al, 1988;Nishi and Miyake, 1989), this was not confirmed by recent studies (Buckley et al, 1994;Petridou et al, 1997). Hence, if a negative association between routine immunizations and the occurrence of childhood acute leukaemia exists, we assume it to be weak as implied by the risk estimates for older children.…”
Section: Discussionmentioning
confidence: 60%
“…Zheng et al (1993) reported an association between appendectomy, tonsillectomy and adult leukaemia. If the inverse association between allergies of the child and acute leukaemia, also observed by Nishi and Miyake (1989) and Petridou et al (1997), is not due to reporting bias, the protective effect of allergies could be interpreted as a proxy for a well-functioning, even overreacting immune system. Since for allergies there seems to exist a genetic predisposition and children of parents with allergies tend to develop an allergy (Daniels et al, 1996), the result, for maternal allergies especially, is not surprising and might be less influenced by recall bias than that for allergies of the child.…”
Section: Discussionmentioning
confidence: 99%